A Stylistic Analysis of Oscar Wilde’s the Nightingale and the Rose - Jalal Abbas, Aswan; Kadir Mugair, Sarab (Opción, 2019)
This tale of Oscar Wilde as other Oscar Wilde’s short tales, was written in an aesthetic manner. Via this work, the author uses distinctive stylistic ele- ments for the explanation of attractive and artistic expression as well. In this study, the attention moves to discovering the artistic and expressive elements which offer characteristics on a composition of the mentioned writer. The wonderful selection of utterances of the writer gives richness to his language, while the uses for innovative articulation and sentence structure gives his style the uniqueness. The stylistic devices used by Oscar Wild give his literary work coherence and cohesion i.e., they make his work sensible, reasonable and acceptable. He treats the stylistic elements in a manner that give his style deviation from the language norm which in turn make his style different from others. To exhibit how Oscar Wilde attracts his readers’ attention he uses various approaches of stylistics, so the analysis of present study shows notions of stylistics taken from Xu Youzhi’s book English Stylistics (2005), as its model. The study also gives a brief introduction of Oscar Wilde and the short story The Nightingale and the Rose. After that , the present study with the solid references expresses certain hypothesis and an extensive elabo- rate investigation of the mentioned story including lexicon, syntax, semantic, phonology and contextual c. Hence, the study will, in general, give a concise articulation of condensing the stylistic devices, which help Oscar Wilde make his work effectively digests and effects anyone who reads it.